1988
DOI: 10.1246/bcsj.61.1057
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidation of the Evaporated Films of Polycyclic Aromatic Hydrocarbons Studied by X-Ray Photoelectron Spectroscopy

Abstract: Photooxidations of the evaporated films of rubrene, naphthacene, and pentacene were investigated by means of X-ray photoelectron spectroscopy. A rubrene film was found to be photooxidized far more easily than a naphthacene film although the molecules of rubrene and naphthacene in solution are known to be almost equally reactive for photooxidation. Although pentacene is photooxidized very easily in solution, the oxidation rate of a pentacene film was little enhanced by the light irradiation. Discussion is given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 26 publications
1
75
0
Order By: Relevance
“…459 Such photo oxidation effects are well-known for condensed materials like rubrene and naphthacene as well. 259 As expected, photoinduced reactions with oxygen were already discovered for illumination experiments with UV 460,461 as well as for the visible part of the light. 128,129,462 Many OLED materials, for example, α-NPD and TPD, are known to degrade (changes in their absorption and PL emission characteristics) after UV irradiation (365 nm, 150 W Hg arc lamp) of single layers in air.…”
Section: Photochemical Reactionssupporting
confidence: 58%
“…459 Such photo oxidation effects are well-known for condensed materials like rubrene and naphthacene as well. 259 As expected, photoinduced reactions with oxygen were already discovered for illumination experiments with UV 460,461 as well as for the visible part of the light. 128,129,462 Many OLED materials, for example, α-NPD and TPD, are known to degrade (changes in their absorption and PL emission characteristics) after UV irradiation (365 nm, 150 W Hg arc lamp) of single layers in air.…”
Section: Photochemical Reactionssupporting
confidence: 58%
“…Earlier researchers have shown that illumination increases the oxidation of rubrene thin films. They also used a source of radiation in the UV to visible range 29,30 . After each exposure, the sample was characterized using XPS and UPS spectroscopies.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…[15,16] Many pentacene OFETs have achieved mobilities more than 1.0 cm 2 V 21 s 21 , depending on the fabrication conditions. [17][18][19][20][21] Although pentacene has an excellent performance for charge transport, it is sensitive to oxygen and light, and has a poor solubility, [22] which limit its application. Many attempts have been made to improve the stability and charge transport properties of pentacene by substrate modification or functionalization of the molecular structure.…”
Section: Introductionmentioning
confidence: 99%